2015
DOI: 10.3109/00365521.2015.1056224
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in ATP-binding cassette transporter genes and interaction with diet and life style factors in relation to colorectal cancer in a Danish prospective case-cohort study

Abstract: Our results suggest that the ABC transporters P-glycoprotein/multidrug resistance 1 and BRCP, in cooperation with IL-10, are involved in the biological mechanism underlying the protective effect of fiber intake in relation to CRC. These results should be replicated in other cohorts to rule out chance findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 85 publications
(119 reference statements)
0
21
0
Order By: Relevance
“…Baseline characteristics of CRC cases and subcohort members including CRC risk factors are presented in Table 2 as published previously (24,25,28,29). Among subcohort members, the genotype distributions of the studied polymorphisms were in HardyWeinberg equilibrium (results not shown).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Baseline characteristics of CRC cases and subcohort members including CRC risk factors are presented in Table 2 as published previously (24,25,28,29). Among subcohort members, the genotype distributions of the studied polymorphisms were in HardyWeinberg equilibrium (results not shown).…”
Section: Resultsmentioning
confidence: 97%
“…A number of persons were excluded: 108 for whom genotype data were missing and 198 with missing information on relevant diet and lifestyle factors (including 3 persons counting as both cases and subcohort members), resulting in a total of 897 CRC cases and 1689 subcohort members for subsequent analyses with full information on both genotype and potential confounders (see flow chart of the study group in Supplemental Figure 1). The present study group has been described previously (24,25,28).…”
Section: Follow-up and Endpointsmentioning
confidence: 99%
“…This may be attributed to an insufficient number of incident cancer cases during the follow‐up period, and some specific risk factors or unknown confounders that were unadjusted. Previous studies have demonstrated gene‐lifestyle (eg, gene‐smoking) interactive effects on cancer risk . The current study did not analyze these genetic effects on cancer risk, which also might be something that affects the results of the association between lifestyle patterns and incidence of cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, many investigations have reported that ABCB1 genetic mutations have a substantial influence on immune responses and apoptosis, and are associated with the development of various malignancies, including colorectal, breast, and lung cancer, hepatocellular carcinoma, and non-Hodgkin lymphoma (Kim et al, 2014;Wan et al, 2014;Gutierrez-Rubio et al, 2015;Kopp et al, 2015;Zhu et al, 2015). For instance, Kim et al (2014) carried out a population-based study of 694 non-Hodgkin lymphoma patients and 1700 controls, reporting that the ABCB1 C3435T polymorphism may contribute to the risk of developing this disease in Koreans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wan et al (2014) demonstrated that the ABCB1 A1564T sequence variation in this gene may affect susceptibility to hepatocellular carcinoma. Kopp et al (2015) conducted an investigation involving 1010 colorectal cancer patients and 1829 control subjects, the results of which suggested that ABCB1 C3435T is involved in the biological mechanism underlying carcinogenesis in the colorectum. Similarly, Gutierrez-Rubio et al (2015) revealed that the T allele of this variant significantly increases breast cancer risk; however, Zhu et al (2015) found no significant relationship between this polymorphism and lung cancer.…”
Section: Discussionmentioning
confidence: 99%